Nesting biology of Black-shouldered Kite ( Elanus caeruleus ) in oil palm landscape in Carey Island, Peninsular Malaysia - Ramli, Rosli; Fauzi, Aimi (Elsevier, 2018)
Black-shouldered Kite (Elanus caeruleus) is a well-known raptor that inhabits open areas such as oil palm plantation or paddy field. To determine preferable habitat and nesting site of Black-shouldered Kite in oil palm landscape, we conducted a study on Black-shouldered Kite's nesting biology in Carey Island, Selangor, Malaysia. We divided the island into six types of habitat and conducted road-side count of Black-shouldered Kite from April 2009 to February 2011. Whenever the Black-shouldered Kite was detected, we thoroughly searched the surrounding area for their nest. In total, we have recorded forty nests. The nests were built on 15 species of trees but most of the trees shared common physical characteristics. Some novice breeders also used oil palm tree as their nesting site. Structure and building materials of nests constructed on oil palm trees were different from nests built on other trees. Of all breeding attempts, only four nests which were located in residential area adjacent to young oil palm habitat were successful. Among important characteristics of successful nesting site include taller trees with strong branches and good leaf coverage. These trees not only protect nests from predator detection (except from other predatory birds) and physical environment but also facilitate Black-shouldered Kite's foraging activities by providing good vantage point.